POVERTY ALLEVIATION BASED ON PARTICIPANT NEEDS AND LOCAL RESOURCES: THE CASE OF PALEMBANG CITY AND OGAN KOMERING ILIR REGENCY - Dian Novriadhy; Niken Probowati Nur Rahayu (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2019)
Abstract The research aimed to test the 2015 Integrated Data Base (IDB) reliability as a source in selecting poverty alleviation program’s target and to develop community's empowerment model. The research conducted in 12 Kelurahan in Palembang City and 2 villages in Ogan-Komering-Ilir Regency from February 2017 to November 2018. Two-hundred-and-fifty-six participants were systematically selected from the 2015 IDB list. The data collected through FGD, interviews and participatory observation. The data analyzed and interpreted based on the input-process-output approach. The research used three stages i.e. problem formulation, system’s components identification, and empowerment model development. The research showed the use of the 2015 IDB resulted in 44.53% right-on-target within range 14.29 to 73.68% per kelurahan/village. The replacement of the targeted participant tended not in the 2015 IDB list. The unfamiliarity of Head of RT to the 2015 IDB suspected as the cause. The replacement was caused by: had moved to another location (91.74%), already work (4.13%), impaired health (3.30%) and died (1%). The participant with different education level had an equal chance to accept empowerment program. The influence of the community’s leader was an important factor in the empowerment program. The reliability of the 2015 IDB depended on the ability of program manager in diminishing of identity politics at the location. To increase the responsiveness, the community's assets also need to be developed alongside individual assets. The empowerment program is indeed an iterative process rather than linear, the program manager should aware of the constant changing of the participant needs. Keywords: